2017
DOI: 10.4238/gmr16039789
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Multiple genetic resistances in Capsicum spp.

Abstract: ABSTRACT. This study aimed to identify Capsicum genotypes with resistance to bacterial spot (BS), anthracnose and Pepper yellow mosaic virus (PepYMV). Fifty-four genotypes of Capsicum spp were evaluated. Resistance reaction against BS was evaluated using three replicates, testing hypersensitivity and quantitative resistance in leaves. After evaluation, inoculated leaves were detached from the plants, being then cultivated until reproductive stage for evaluations anthracnose resistance in immature and mature fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…UENF 1381 is a Capsicum annuum var annuum accession from the UENF genebank, it is pungent and identified as resistant to bacterial spot [9] and anthracnose. ‘Ikeda’ is a very traditional sweet pepper ( Capsicum annuum ) genotype that has been used by small farmers for a long time, and it is susceptible to bacterial spot and also to anthracnose [10].…”
Section: Methodsmentioning
confidence: 99%
“…UENF 1381 is a Capsicum annuum var annuum accession from the UENF genebank, it is pungent and identified as resistant to bacterial spot [9] and anthracnose. ‘Ikeda’ is a very traditional sweet pepper ( Capsicum annuum ) genotype that has been used by small farmers for a long time, and it is susceptible to bacterial spot and also to anthracnose [10].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies identifying sources of resistance in Capsicum species in response to Colletotrichum spp. infection showed that ripe fruits are more resistant to anthracnose compared to unripe www.nature.com/scientificreports/ fruits 17,[40][41][42] . This could be explained by the rapidly induced expression of CaEAS and CaEAH genes in response to C. scovillei in ripe pepper fruits, while in unripe fruits a late and high upregulation of capsidiol biosynthetic genes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Capsicum annuum accession from GBUEL103 (susceptible) and GBUEL104 (resistant to bacterial spot, pepper yellow mosaic virus, and anthracnose 41 ) were obtained from the Universidade Estadual de Londrina (UEL) seed germplasm. Samples were sown on a tray with organic plant substrates and, after the emergence of two pairs of true leaves, seedlings were transferred individually to plastic pots containing a mixture of soil and substrate (2:1, w:w ratio).…”
Section: Methodsmentioning
confidence: 99%
“…against to anthracnose caused by Colletotrichum spp. (Parey et al, 2013;Begum et al, 2015;Arunakumara and Satyanarayana, 2016;Bento et al, 2017;Maracahipes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%